Teacher collaborative inquiry in the context of literacy education: examining the effects on teacher self-efficacy, instructional and assessment practices. Issue 7 (2nd October 2016) - Ciampa, Katia; Gallagher, Tiffany L.
Abstract: This case study research reports on elementary (grade 8) and secondary school (grade 9) teachers' participation in job-embedded, professional learning and engagement in collaborative inquiry. Teachers constructed an inquiry-oriented media literacy unit following the collaborative inquiry model. The current study sought to investigate how collaborative inquiry influenced their self-efficacy in literacy instruction, instructional and assessment practices. Qualitative data sources included researchers' anecdotal notes, teacher interviews, and professional learning blog conversations. Inductive analyses of the data generated six major themes comprising enhancements to teachers' literacy instructional and assessment practices, which were evident in their adoption of the backward-design model, use of success criteria, and greater emphasis on diagnostic and formative assessment. With respect to teachers' self-efficacy, data analyses also revealed increased levels of intrinsic motivation, professional satisfaction, and reflective practice. This study provides evidence for the transformative potential and characteristics of school-based teacher collaborative inquiry and the resultant impacts on teacher learning.